Acute infectious purpura fulminans: case report of a medical emergency - Xueying Li; Yaqian Ma; Qichao Sun; Ruihan Hu; Zhi Liu; Xiaowei Liu (Emergency and Critical Care Medicine)
Abstract. Background. Purpura fulminans (PF), characterized by the sudden onset of large, rapidly spreading hemorrhagic skin infarctions and associated disseminated intravascular coagulation, is an uncommon medical emergency. Early recognition, prompt antibiotic therapy, and intensive supportive care are essential to reduce the mortality rate of this disease. Case Presentation. We report the case of a 28-year-old Chinese man with acute infectious PF. He initially presented with a fever, which rapidly progressed to septic shock, followed by skin lesions and disseminated intravascular coagulation. Computed tomography imaging revealed superior and inferior mesenteric vein thromboses. Although the etiology of the patient’s infection was unclear, the patient received early fluid resuscitation, empiric antibiotic therapy, and blood product replacement, which resulted in gradual clinical improvement. Conclusion. Sepsis-associated PF may be reversible with timely empirical therapeutic interventions; however, the severity of PF should not be underestimated, and treatment should be tailored to individual patients.